The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fimmu.2022.900793
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Nutrition in Songpu Mirror Carp (Cyprinus carpio Songpu) During Chronic Carbonate Alkalinity Stress: Effects on Growth, Intestinal Immunity, Physical Barrier Function, and Intestinal Microflora

Abstract: Carbonate alkalinity is a major environmental stress factor affecting aquatic feed configuration, which easily causes oxidative stress and hypoimmunity for fish. Hence, the purpose of the study is to assess the potential effect of phosphorus on growth, intestinal oxidation resistance, physical barrier function, and microflora for Songpu mirror carp (Cyprinus carpio Songpu) (initial average weight of 2.95 ± 0.21 g) reared at the high-concentration carbonate alkalinity environment. A two-factor, three-level (2 ×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…Similar results were also observed in crucian carp (Carassius auratus) [30], grass carp (Ctenopharyngodon idella) [31], and rainbow trout (Oncorhynchus mykiss) [32]. In addition, a study on Songpu Mirror Carp (Cyprinus carpio Songpu) found that P supplementation in the diet promoted intestinal health and feed utilization [33]. In this study, it was also found that an available P level of 0.71% diet significantly increased the feed utilization of spotted seabass compared to a basal diet with an available P level of 0.35%, which was probably responsible for the improvement in fish growth.…”
Section: Discussionsupporting
confidence: 65%
“…Similar results were also observed in crucian carp (Carassius auratus) [30], grass carp (Ctenopharyngodon idella) [31], and rainbow trout (Oncorhynchus mykiss) [32]. In addition, a study on Songpu Mirror Carp (Cyprinus carpio Songpu) found that P supplementation in the diet promoted intestinal health and feed utilization [33]. In this study, it was also found that an available P level of 0.71% diet significantly increased the feed utilization of spotted seabass compared to a basal diet with an available P level of 0.35%, which was probably responsible for the improvement in fish growth.…”
Section: Discussionsupporting
confidence: 65%
“…Extensive studies have demonstrated that variations in salinity, alkalinity, dissolved oxygen, temperature, and ammonia nitrogen within the aquatic environment can induce defense responses in organisms, including oxidative stress responses [15][16][17][18]. Under such stress conditions, the continuous production of ROS can disrupt the balance between the oxidative and antioxidant system, inflicting oxidative damage on lipids, proteins, DNA, and carbohydrates.…”
Section: Discussionmentioning
confidence: 99%
“…Carbonate alkalinity, a significant environmental stressor that can swiftly cause oxidative stress and hypo immunity in fish, substantially impacts the structure of aquatic feed. In addition to exerting effects on the growth, immunity, and disease resistance of aquatic organisms, prolonged exposure to carbonate alkalinity stress can also influence the in-vivo nutrition metabolism of fish (Fan et al, 2021(Fan et al, , 2022.…”
Section: Alkalinity Oxidative Stress and Fish Healthmentioning
confidence: 99%